2007
DOI: 10.1523/jneurosci.2506-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Coincident Activation of Metabotropic Glutamate Receptors and NMDA Receptors (NMDARs) Downregulates Perisynaptic/Extrasynaptic NMDARs and Enhances High-Fidelity Neurotransmission at the Developing Calyx of Held Synapse

Abstract: The expression of this downregulation depends on ongoing synaptic activity, and is attenuated by a dynamin peptide (D15) that blocks clathrindependent internalization. We further demonstrated that the same induction paradigm specifically reduces NMDAR-dependent plateau potential and aberrant spike firings during repetitive activity. Together, our results suggest that coincident activation of mGluRs and NMDARs during intense synaptic activity may lead to selective endocytosis of NMDARs in the perisynaptic/extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 43 publications
3
28
1
Order By: Relevance
“…During high-frequency bursting, MNTB neurons demonstrated a plateau depolarization in vivo. Plateau depolarizations have also been observed during high-frequency calyceal stimulation in slice recordings, and were shown to be NMDA-dependent (Futai et al 2001;Leão & von Gersdorff, 2002;Joshi et al 2007) and attenuated by presynaptic activation of adrenergic receptors (Leão & von Gersdorff, 2002). Our simulations in which we used the recorded VC activity as input to the HH-model were in agreement with an important role for NMDAR activity, even though for definitive confirmation pharmacological blockage would be needed.…”
Section: Plateau Potentialssupporting
confidence: 61%
See 1 more Smart Citation
“…During high-frequency bursting, MNTB neurons demonstrated a plateau depolarization in vivo. Plateau depolarizations have also been observed during high-frequency calyceal stimulation in slice recordings, and were shown to be NMDA-dependent (Futai et al 2001;Leão & von Gersdorff, 2002;Joshi et al 2007) and attenuated by presynaptic activation of adrenergic receptors (Leão & von Gersdorff, 2002). Our simulations in which we used the recorded VC activity as input to the HH-model were in agreement with an important role for NMDAR activity, even though for definitive confirmation pharmacological blockage would be needed.…”
Section: Plateau Potentialssupporting
confidence: 61%
“…; Leão & von Gersdorff, ; Joshi et al . ) and attenuated by presynaptic activation of adrenergic receptors (Leão & von Gersdorff, ). Our simulations in which we used the recorded VC activity as input to the HH‐model were in agreement with an important role for NMDAR activity, even though for definitive confirmation pharmacological blockage would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a number of models of delayed neurodegeneration imply that persistent downregulations of glutamate subunit types which permit increases in Ca 2+ permeability also occur in surviving cells of the retina, hippocampus, and spinal cord (Hof et al, 1998; Grossman et al, 1999; Vandenberghe et al, 2000). Additionally, prolonged application of NMDA can alter coupling of synaptic and perisynaptic/extrasynaptic NMDARs to group I mGluRs to influence the dynamics of NMDAR trafficking at the synapse (Joshi et al, 2007). In keeping with this, cultured retinal ganglion cells (RGCs) are resistant to direct application of NMDA and glutamate due to NMDA receptors being expressed extrasynaptically (Ullian et al, 2004), although RGCs are vulnerable after retinal ischemia and in glaucoma (Sucher et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We consider a possibility that PTP contributes to the maturation of calyx of Held synapse. Recently, Joshi et al (2007) reported that extrasynaptic NMDA receptors (NMDARs) are downregulated by pairing a depolarization of the postsynaptic neuron and burst stimulation of afferent axon fibers, probably by the mechanism of coincident activation of postsynaptic metabotropic glutamate receptors and NMDARs. It remains to be addressed whether such strong stimuli are possible under physiological conditions during a developmental period of hearing onset.…”
Section: Possible Physiological Role Of Ptp In Development Of Calyx Omentioning
confidence: 99%